2022
DOI: 10.1109/tro.2022.3158194
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Turning Maneuver of a Many-Legged Robot Using Pitchfork Bifurcation

Abstract: Legged robots have excellent terrestrial mobility for traversing diverse environments and, thus, have the potential to be deployed in a wide variety of scenarios. However, they are susceptible to falling and leg malfunction during locomotion. Although the use of a large number of legs can overcome these problems, it makes the body long and leads to many legs being constrained to contact with the ground to support the long body, which impedes maneuverability. To improve the locomotion maneuverability of such ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(14 citation statements)
references
References 56 publications
(77 reference statements)
2
12
0
Order By: Relevance
“…Our previous study 43 revealed that when all the spring constants for the body-segment yaw joints are reduced, the straight walk becomes unstable through Hopf bifurcation (this bifurcation changes the stability of an equilibrium point in a dynamical system by changing a parameter and creating a limit cycle 46 ), and body undulations appear, which was verified by a Floquet analysis with a simple robot model. In addition, another previous study 42 revealed that when only the spring constant k 1 for yaw joint 1 is reduced, the straight walk transitions into a left- or right-curved walk through pitchfork bifurcation (this bifurcation changes the stability of an equilibrium point and creates two equilibrium points 46 ), which was also verified by a Floquet analysis with a simple robot model.…”
Section: Instability and Bifurcation Of Straight Walkingsupporting
confidence: 52%
See 3 more Smart Citations
“…Our previous study 43 revealed that when all the spring constants for the body-segment yaw joints are reduced, the straight walk becomes unstable through Hopf bifurcation (this bifurcation changes the stability of an equilibrium point in a dynamical system by changing a parameter and creating a limit cycle 46 ), and body undulations appear, which was verified by a Floquet analysis with a simple robot model. In addition, another previous study 42 revealed that when only the spring constant k 1 for yaw joint 1 is reduced, the straight walk transitions into a left- or right-curved walk through pitchfork bifurcation (this bifurcation changes the stability of an equilibrium point and creates two equilibrium points 46 ), which was also verified by a Floquet analysis with a simple robot model.…”
Section: Instability and Bifurcation Of Straight Walkingsupporting
confidence: 52%
“…The developed robot 43 was later improved. 42 , 44 In this study, the robot newly incorporated a variable stiffness mechanism. This robot is composed of six modules (modules 1–6).…”
Section: Myriapod Robotmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, bifurcation phenomena have been observed in areas other than walking motion. Aoi et al demonstrated the advanced turning maneuvers of a multilegged centipede robot using the bifurcation phenomenon as a parameter of the flexibility of its body segments [40]. In a study of bifurcated gait transitions, a semi-autonomous control system with two bifurcated attractors was proposed [41].…”
Section: Introductionmentioning
confidence: 99%